(untitled) (Sebha University Conference Proceedings, 2024)
This study aimed to examine the influence of an inhibitor, Ziziphus spina Christi (ZSC) leaves, on the corrosion of medium carbon steel in 0.5 M Hydrochloric acid (HCl) solution over the temperature at 30 and 60 °C by weight loss measurements. Chemical analysis has been used to determine the impact of adding hydrochloric acid on the corrosion and corrosion inhibition of mild steel in 0.5 M hydrochloric acid (HCl) at 30 and 60 °C in the absence and presence of aqueous and alcoholic extracts of (ZSC) plant. The efficiency of corrosion inhibition was assessed using a weight loss measurement method. The standard approach to measuring the weight loss of metal cylinders exposed to corrosive environments is called laboratory immersion corrosion testing. At both temperatures of 30 °C or 60 °C, it has been discovered that the effects of inhibitor concentration on the corrosion rate of low steel increase with inhibitor concentration. To find the most accurate isothermal equilibrium data set models for the employed inhibitor, experimental data was used. All of the employed adsorption isotherms, such as the Temkin and Langmuir isotherms, fit the results, although applying an alcohol extract inhibitor at 60 °C showed a slight improvement.